Risk-adjusted and Bonferroni-adjusted seasonality in emerging Asian stock markets - Faheem Aslam; Bilal Ahmed Memon; Khurram Shahzad Mughal (Universitas Islam Indonesia, 2020)
Existing literature on market seasonality focuses mainly on returns anomalies with little or no attention to risk adjustment. This study investigates risk-adjusted, and Bonferroni adjusted day-of-the-week anomalies in nine emerging Asian stock markets. The data consist of the daily prices of nine stock indices from January 1997 to September 2019. The MSCI emerging market index was employed as a proxy of time-varying risk. Findings/originality: The results confirm the presence of day-of-the-week anomalies in emerging Asian markets, and the addition of the market risk proxy has failed to fade these patterns. Finally, after consideration of time-varying risk premium and applying Bonferroni Correction type adjustment, several market anomalies remain. However, both adjustments partially eliminate the significance of these patterns. The presence of these anomalies suggests that little of this can be accounted for the MSCI-EM stock price index. The results also confirm that systematic risk level varies from Monday to Friday.